1993
DOI: 10.1002/ijc.2910550211
|View full text |Cite
|
Sign up to set email alerts
|

Invasive squamous‐cell cervical carcinoma and combined oral contraceptives: Results from a multinational study

Abstract: Data from a hospital-based case-control study collected in I I participating centers in 9 countries were analyzed to determine whether use of combined oral contraceptives alters risk of invasive squamous-cell cervical cancer. Information on prior use of oral contraceptives, screening for cervical cancer, and suspected risk factors for this disease were ascertained from interviews of 2361 cases and 13,644 controls. A history of smoking and anal and genital warts was obtained, and blood specimens were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The contraceptive depo-medroxyprogesterone (DMPA) is an injectable form of progestin that is given every 3 months for pregnancy protection in humans. DMPA and spermicide such as N-9 have been reported to change the genital tract microenvironment and cause the vagina and cervix to be more susceptible to viral infection and persistence [ 48 , 49 , 50 , 51 ]. Vaginal epithelial cells of mature female mice responded to changing levels of estrogens and progesterone during a 4–5-day estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The contraceptive depo-medroxyprogesterone (DMPA) is an injectable form of progestin that is given every 3 months for pregnancy protection in humans. DMPA and spermicide such as N-9 have been reported to change the genital tract microenvironment and cause the vagina and cervix to be more susceptible to viral infection and persistence [ 48 , 49 , 50 , 51 ]. Vaginal epithelial cells of mature female mice responded to changing levels of estrogens and progesterone during a 4–5-day estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The possible association between the use of OCP and the development of cervical neoplasia has been the subject of many epidemiological investigations, but the nature of the association remains unclear [9]. In 1993 a massive worldwide study conducted by the World Health Organization, was published which examined the risk established between OCP use and invasive squamous cervical carcinoma among 2300 women who had cervical carcinoma and found a strong correlation [10]. In a large study group, Herrero et al showed that women who had received injectable progestins for at least 5 years and who had used them at least 5 years ago suffered a 430% increased risk of developing cervical cancer [11].…”
Section: Discussionmentioning
confidence: 99%
“…Human papillomavirus 16, the most important cause of cervical cancer, contains a progesterone/glucocorticoid response element upstream to the common E6/E7 promoter,14 and progesterone enhances the ability of the viral DNA to transform cells 15. In fact, papillomavirus lesions are exacerbated during pregnancy16 and risk of cervical cancer is increased by oral contraceptives and pregnancy when progestogen levels are high 1 3 4 17. Oestrogen increases human papillomavirus expression by upregulation of the progesterone receptor 18.…”
Section: Discussionmentioning
confidence: 99%